(untitled) (London Journal of Medical and Health Research, 2025)
Background: Acute Invasive fungal rhinosinusitis (AIFR) is a life-threatening disease presents usually in immune-compromised patients with impaired neutrophilic response. Aim: To study and statistically analyze the epidemiological factors leading to the observed increased incidence of invasive fungal rhinosinusitis in coronavirus disease-19 (COVID-19) diseased patients and identify the prognostic factors that may affect the course and outcome of the disease. Methods: This case-control study was carried out on 23 patients diagnosed with acute invasive fungal sinusitis patients, patients with positive coronavirus or recently recovered from coronavirus infection admitted to tertiary or secondary centers in El-Gharbia governorate, and 46 participants as a control. The study was focused on the epidemiological predisposing factors that may affect the incidence of the disease. Results: COVID-19 reporting and data system (CORAD), level of O2 saturation, PH, steroid therapy dose and duration, duration of O2 therapy, and anterior septal deviation were insignificantly different between the two studied groups. Random blood sugar (RBS), neutropenia, and type O2 therapy were significantly different between the two studied groups. Steroid therapy dose and duration were significantly higher in the patients’ group than control group (P